EIGENVALUE LINEAR BUCKLING OPTIMIZATION OF MODIFIED OPEN WEB STEEL JOIST - Ardianto, Johan (Jurnal Teknik Sipil, 2018)
Abstract: Open web steel joist (OWSJ) is a lightweight beam structural system that is widely used since the 1900s. It generally composed by T section as flanges on top and bottom, and L sec-tion as an open web on the centre. However, many modifications of OWSJ is commonly seen in construction sites, one of them is the usage of channel sections as top and bottom flange, and rebar steel as the open web. This configuration is mainly used to reduce cost and ease the material sup-ply. The modified OWSJ have potential to act differently than the regular one, hence scientific study need to performed to know the behaviour of the modified system. In this paper, comparison on analytical and finite element approach is conducted. The analytical method is done by mechani-cal calculation assuming there are no buckling of the flanges, web rebars are calculated individual-ly. In real structure, buckling may occur and web rebars also work concurrently. Therefore, finite element analysis with LUSAS software is conducted. The purpose of this research is to know the behaviour of OWSJ in FEM analysis. Result displays lateral torsional buckling is happen and to overcome this problem, gradation of web size is tested, resulting maximum of 10.6 % increase in capacity.